Clinical and laboratory correlates of lung disease and cancer in adults with idiopathic hypogammaglobulinaemia. (27th January 2016) - Brent, J.; Guzman, D.; Bangs, C.; Grimbacher, B.; Fayolle, C.; Huissoon, A.; Bethune, C.; Thomas, M.; Patel, S.; Jolles, S.; Alachkar, H.; Kumaratne, D.; et al.
Summary: Idiopathic hypogammaglobulinaemia, including common variable immune deficiency (CVID), has a heterogeneous clinical phenotype. This study used data from the national UK Primary Immune Deficiency (UKPID) registry to examine factors associated with adverse outcomes, particularly lung damage and malignancy. A total of 801 adults labelled with idiopathic hypogammaglobulinaemia and CVID aged 18–96 years from 10 UK cities were recruited using the UKPID registry database. Clinical and laboratory data (leucocyte numbers and serum immunoglobulin concentrations) were collated and analysed using uni‐ and multivariate statistics. Low serum immunoglobulin (Ig)G pre‐immunoglobulin replacement therapy was the key factor associated with lower respiratory tract infections (LRTI) and history of LRTI was the main factor associated with bronchiectasis. History of overt LRTI was also associated with a significantly shorter delay in diagnosis and commencing immunoglobulin replacement therapy [5 (range 1–13 years) versus 9 (range 2–24) years]. Patients with bronchiectasis started immunoglobulin replacement therapy significantly later than those without this complication [7 (range 2–22) years versus 5 (range 1–13) years]. Patients with a history of LRTI had higher serum IgG concentrations on therapy and were twice as likely to be on prophylactic antibiotics. Ensuring prompt commencement of immunoglobulin therapy in patients with idiopathic hypogammaglobulinaemia is likely to help prevent LRTI and subsequent bronchiectasis. Cancer was the only factor associated with mortality. Overt cancer, both haematological and non‐haematological, was associated with significantly lower absolute CD8 + T cell but not natural killer (NK) cell numbers, raising the question as to what extent immune senescence, particularly of CD8 + T cells, might contribute to the increased risk of cancers as individuals age.